2017
DOI: 10.1016/s1473-3099(16)30257-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of carbapenemase-producing Klebsiella pneumoniae and Escherichia coli in the European survey of carbapenemase-producing Enterobacteriaceae (EuSCAPE): a prospective, multinational study

Abstract: SummaryBackground Gaps in the diagnostic capacity and heterogeneity of national surveillance and reporting standards in Europe make it diffi cult to contain carbapenemase-producing Enterobacteriaceae. We report the development of a consistent sampling framework and the results of the fi rst structured survey on the occurrence of carbapenemaseproducing Klebsiella pneumoniae and Escherichia coli in European hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
365
10
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(439 citation statements)
references
References 21 publications
20
365
10
17
Order By: Relevance
“…VIM has declined, from being the exclusive carbapenemase detected in Greece until 2006 [1], to 8.4% in 2016 and is followed by double carbapenemase production (5.6%) and OXA-48 (3.6%). These findings are in accordance with those from the European Survey on Carbapenemase-Producing Enterobacteriaceae (EuSCAPE) project, conducted between November 2013 and April 2014, in which Grundmann et al reported for the first time that NDM was the second-ranking carbapenemase in Greece [26]. In a previous published nationwide surveillance study from January 2011 to June 2012, among 119 Greek hospitals, the prevalent mechanism of carbapenem resistance in K. pneumoniae isolates was KPC (82.6%), followed by VIM (9.7%), while the concurrent production of KPC and VIM was noted in 7.7% of the isolates [27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…VIM has declined, from being the exclusive carbapenemase detected in Greece until 2006 [1], to 8.4% in 2016 and is followed by double carbapenemase production (5.6%) and OXA-48 (3.6%). These findings are in accordance with those from the European Survey on Carbapenemase-Producing Enterobacteriaceae (EuSCAPE) project, conducted between November 2013 and April 2014, in which Grundmann et al reported for the first time that NDM was the second-ranking carbapenemase in Greece [26]. In a previous published nationwide surveillance study from January 2011 to June 2012, among 119 Greek hospitals, the prevalent mechanism of carbapenem resistance in K. pneumoniae isolates was KPC (82.6%), followed by VIM (9.7%), while the concurrent production of KPC and VIM was noted in 7.7% of the isolates [27].…”
Section: Discussionsupporting
confidence: 91%
“…The Greek situation differs greatly from other European countries such as Spain, France, Germany, Turkey, Romania and Belgium, where OXA-48, most often linked with community-onset healthcare associated sources, is the most frequently encountered carbapenemase [26,[28][29][30][31].…”
Section: Discussionmentioning
confidence: 97%
“…The boom of international travel and tourism from China to Europe and other countries may increase the opportunities for colonization of travelers. The fact that OXA-48-producing strains have nearly outcompeted KPC and NDM producers and have become the most common CRE in several countries in Europe is alarming (11,12). These data support the need for surveillance studies, such as screening of patients who were recently hospitalized in regions of OXA-48 endemicity and were then admitted to Chinese hospitals.…”
mentioning
confidence: 66%
“…In part due to the difficulty of effectively treating infections with CRE, mortality rates can be as high as 40 to 50% (6). These infections are a worldwide problem, with recent reports indicating that CRE are widespread in the United States (7), Europe (8), and China (9). Unfortunately, resistance to "last-line" drugs, such as colistin, is emerging in CRKP strains, and in some cases, isolates are resistant to all antibiotics tested (10).…”
mentioning
confidence: 99%